EFEKTIVITAS PENGGUNAAN APLIKASI PENDAMPING PARIWISATA DI KAWASAN TAMAN MARGASATWA RAGUNAN - Ramadhan, Aula; Vitha Octavanny; Riza Firmansyah (Journal of Tourism Destination and Attraction, 2024)
This research aims to analyze usability tests and satisfaction factors for visitors who use the Taman Margasatwa Ragunan application and identify satisfaction levels based on the Customer Satisfaction Index (CSI). The method used in this research is descriptive with quantitative methods. The object of this research is Usability Testing (Learnability, efficiency, memorability, error) and visitor satisfaction and satisfaction factors (product quality, service quality, emotional image, price and cost). The sample obtained was 100 respondents using a purposive sampling technique and using data collection methods in the form of questionnaires, literature studies and documentation. Based on the research results, analyze of usability testing attributes and visitor satisfaction factor attributes shows that the Taman Margasatwa Ragunan application is easy to use and meets user needs so as to meet the satisfaction of visitors who use the application. This is proven by the large number of respondents who filled in “Important and Very Important” also “Satisfied and Very Satisfied” statements regarding the identification of Usability Testing and user satisfaction factors in the Taman Margasatwa Ragunan application. This is reinforced by the results of the CSI calculation with a value of 79.35% which is based on the CSI value index table in the "SATISFIED" criteria. This shows that the majority of visitors who use the tourism companion application in the Ragunan Wildlife Park Area are satisfied with all the indicators used in this research.